Application of Problem Based Learning (PBL) Model to Student’s Motivation in Science - M.Yusuf Firduas; Muhammad Aminuddin; Anny Zuliyana (LPPM Institut Studi Islam Sunan Doe, 2024)
Natural Science learning in junior high schools should strive for learning through concrete activities; by presenting natural phenomena in every learning this can increase students' interest in learning. However, in reality, science learning, especially at MTs NW Aik Anyar, still uses conventional learning, making students less motivated in participating in learning. This study aims to determine the increase in science learning motivation of grade VIII students at MTs NW Aik Anyar after the implementation of the Problem Based Learning (PBL) model. This type of research is class action research (PTK) with the subject of the study being grade VIII students with a total of 25 students. Data on students' motivation to learn science was collected by questionnaire. Once the data were obtained, they were analyzed using descriptive statistical analysis. Based on the results of data analysis, in the first cycle, the average motivation to learn science of grade VIII MTs NW Aik Anyar students after participating in learning by applying the Problem Based Learning model was 103.81 and was in the high category. The classical completion percentage is 75%. In the second cycle, the average motivation of students to learn science increased to 119.51 and was in the very high category. The classical completion percentage is 95%. Based on these results, it can be concluded that the Problem Based Learning l model is effectively able to increase students' motivation to learn science.